An Empirical Study on the Impact of Shadow Bank on Macro-economy in China - Zhou, Lei; Cai, Jingjing; Zhou, Jianhui (Economics & Management Review, 2020)
Under the background of ‘Financial Disintermediation’, we study the macroeconomic impact of China’s shadow bank expansion is of great significance for improving the financial supervision system and for preventing and defusing financial risks. By constructing an index system for measuring the size of shadow banks and macroeconomic fluctuations, collecting monthly time series data from February 2011 to March 2019, using the VAR model to perform impulse response analysis, and empirically studying the major macroeconomic indicators of shadow bank expansion Dynamic effects. The study found that the expansion of shadow bank will push up the inflation rate, which is not conducive to stabilizing prices, and will weaken the effectiveness of monetary policy; however, shadow bank also provides supplementary financing channels for small and medium-sized enterprises in the physical sector, which objectively promotes Marketization of Interest Rates. Finally, based on empirical results, policy suggestions such as clearly defining the scope of shadow bank, improving shadow bank risk supervision, optimizing the currency level statistical caliber, unblocking the transmission mechanism of monetary policy, and deepening the reform of interest rate liberalization are proposed.